The Humour and Novelty of Congwayndut Puppet Group: An Overview of Performance Studies - Gendot Dekanipa; Aris Setiawan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
As a dynamic cultural event, the contemporary art of the Congwayndut group is always produced with a unique dramaturgy, contemporary and innovative setting. Congwayndut provides a sense of humour with an all-ages segmentation to entertain audiences. Regarding to the case, this paper attempts to examine performance studies through the use of performance studies reading schemes, social drama theory, and trickster in cultural practice. Through the